Pertumbuhan Misellium Bibit F1 Jamur Tiram(Pleurotus Ostreatus) Dan Jamur Merang (Volvariella Volvaceae) PadaMedia Kacang Hijau Dan Kedelai Hitam Dari Bibit F0Media Biji Nangka - Ekawati, Desy, Dra. Suparti, M.Si (2017)
F1 seedlings are derivatives of a pure F0 culture grown on a medium that typically contains proteins. Generally using grains. Green beans and black soybeans contain (protein, carbohydrate, fat) that can be used as F1 breeding innovation medium and growth of oyster mushroom mushroom. The purpose of this study to determine thegrowth of mycelium seeds F1 oyster mushrooms and mushrooms on the medium of green beans and black soybeans. The most optimal green bean seed medium on mycelium growth. The type of research used in the from of experiments with complete randomized design (RAL) design of factorial patterns implemented in 2 repetitions. Factor 1 green beans : on oyster mushrooms (M1J1), on mushroom (M1J2). Factor 2 black soybeans : on on oyster mushrooms (M2J1), on mushroom (M2J2). Parameters measured were density, thickness, speed of oyster mushroom and mushroom. Technical analysis using quantitative descriptive data. Based on the results obtained on the growth of the mycelium of F1 mushroom and oyster mushroom highest in green bean mediumis 7,5 cm/day, the density is very thick, the nutrient content affecting the growth of mycelium while the growth of the mycelium of F1 mushroom oyster mushroom and mushroom lowest on black soybean medium that is 3,3 cm/day, dencity meeting, thicknees grow not medium